John Murtagh's general practice - Murtagh, John 1936- (The McGraw-Hill Companies, 2011)
John Murtagh's General Practice is widely recognized as the most influential publication for general practice and primary health care. Now in its fifth edition, this gold standard reference comprehensively covers the entire spectrum of general practice.